'Honestly no, I've never looked at it': teachers' understandings and practices related to students' personal data in digitised health and physical education. Issue 3 (3rd July 2021) - Lupton, Deborah
ABSTRACT: In wealthy countries such as Australia, learning and teaching practices in schools have become increasingly digitised as educational technology (EdTech) initiatives gather momentum. This digitisation inevitably involves rendering many dimensions of students' bodies, activities and practices into digital data formats across learning areas: including health and physical education (HPE). These data can be used by schools and third parties to conduct surveillance of students' bodies and learning. This article draws on findings from a project involving interviews with HPE teachers in a diverse array of schools located in eastern Australia about the ways they were using digital technologies for pedagogical purposes. The interviews included questions concerning to what extent the teachers were aware of personal data security and privacy issues related to their students. While the use of datafication technologies such as apps and wearable devices for HPE teaching was common among our participants, for the most part, these teachers were not considering issues such as who could gain access to students' personal information and how these data might be breached or exploited by third parties. These findings are discussed within the broader contexts of young people's personal data privacy rights and schools' role in protecting students' information.